Evaluation of DNA Fragmentation in Goat Spermatozoa Using Acridine Orange Protocols - Hernández-Carrillo, Enrique de Jesús; Cárdenas Padilla, Alberto Jorge; Alcantar Rodríguez, Alicia; Medrano Hernández, José Alfredo (Spei Domus, 2025)
In caprine production systems, evaluation of male fertility is critical to determine female conception rates. However, conventional semen quality parameters fail to reflect sperm dna integrity. Irreversible DNA damage in gametes may occur during spermatogenesis or transit through the reproductive tract. Acridine orange (AO) staining provides a cost-effective method to assess dna fragmentation. Seven Saanen bucks were included in this study. Ejaculates were collected via artificial vagina, and pooled semen samples were analyzed. Semen parameters included mass motility (MM), progressive motility (PM), viability (V), and sperm morphology. dna damage was quantified using two positive controls (NaOH exposure and UV irradiation) and one negative control (fresh semen). Five AO concentrations were tested: 100 μg/ml, 200 μg/ml, 500 μg/ml, 1000 μg/ml, and 2000 μg/ml. Statistical analysis was performed using the proc glm procedure in SAS® University Edition. No significant differences were observed among protocols (p > 0.05). However, AO concentrations ≥500 μg/ml induced detectable dna damage in fresh semen spermatozoa. These results suggest that AO staining at 500 μg/ml is optimal for evaluating sperm dna damage during routine semen quality assessments in caprines.
Keywords: Caprine; semen analysis; DNA fragmentation; acridine orange; sperm quality